Cretaceous large-scale metal accumulation triggered by post-subductional large-scale extension, East Asia - Mao, Jingwen; Liu, Peng; Goldfarb, Richard J.; Goryachev, Nikolai A.; Pirajno, Franco; Zheng, Wei; Zhou, Meifu; Zhao, Chao; Xie, Guiqing; Yuan, Shunda; Liu, Min (Ore geology reviews, 2021)
Large-scale mineralization may occur in large-scale extensional domains along active continental margins. [Display omitted] Effective exploration for ore deposits usually seeks distinct conditions within fundamentally prospective geological settings that might lead to enhanced ore-forming processes. Large-scale metal accumulation to form ore deposits is usually associated with specific tectonic events. Many studies have found that significant mineralization is genetically related to plate subduction and accretion/collision tectonic regimes. Here we describe how an active continental margin extensional setting can also define an important tectonic environment for the development of a world-class regional metallogenic province subsequent to subduction and compressional stresses. The extensive and diverse group of mineral deposits formed from 145 to 70 Ma along the eastern Asian continental margin (EACM), from northern Vietnam, through eastern China, Korea, Japan, and to the Sikhote-Alin region of Far East Russia, represents a good example of a regional extension-related metallogenic province. The varied mineral deposits with distinct fluid and metal sources occur in a series of NE- or NNE-trending pull-apart basins and metamorphic core complexes, as well as along associated transtensional faults, reflecting the controls of an extensional regime. A new tectono-metallogenic model for the Cretaceous ore-forming events of eastern Asia is proposed to highlight the exploration potential in such tectonic settings throughout the world.